2009
DOI: 10.1007/s11164-009-0058-0
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the crystal photochromism of 4,4′-methylenebis{(N-3,5-di-tert-butylsalicylidene)-2,6-dimethylaniline}

Abstract: 4,4 0 -methylenebis{N-(3,5-di-tert-butylsalicylidene)-2,6-dimethylaniline} formed a definite acetone-inclusion crystal by recrystallization with acetone. Through crystal-to-crystal solvent exchange of the crystal, various types of crystals were obtained. All resulting crystals exhibited photochromism. Rate constants of thermal fading of photochromes were found to depend on the number of solvent molecules included in the crystal unit. The thermal stability of photochrome is discussed in connection with molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Kawato et al reported a similar fading process in the case of thermal relaxation of N-salicylidene aniline itself and of its deuterated derivative [16], and also for N-(3-tert-butylsalicylidene)-3-nitro-aniline [16] and 4,4 0 -methylenebis(N-salicylidene-2,6-diisopropylaniline) [17], or 4,4 0 -methylenebis{(N-3,5-di-tert-butylsalicylidene)-2,6-dimethylaniline} [18]. Since we monitored the relaxation process at 564 nm, one could ascribe the two stages of back-isomerisation to two different kinds of trans-keto species.…”
Section: Diffuse Reflectance Spectroscopymentioning
confidence: 66%
“…Kawato et al reported a similar fading process in the case of thermal relaxation of N-salicylidene aniline itself and of its deuterated derivative [16], and also for N-(3-tert-butylsalicylidene)-3-nitro-aniline [16] and 4,4 0 -methylenebis(N-salicylidene-2,6-diisopropylaniline) [17], or 4,4 0 -methylenebis{(N-3,5-di-tert-butylsalicylidene)-2,6-dimethylaniline} [18]. Since we monitored the relaxation process at 564 nm, one could ascribe the two stages of back-isomerisation to two different kinds of trans-keto species.…”
Section: Diffuse Reflectance Spectroscopymentioning
confidence: 66%